Diagnostic Accuracy of Routinely Available Biomarkers to Predict Bacteremia in Children With Community-Acquired Pneumonia: A Secondary Analysis of the GPIP/ACTIV Pneumonia Study in France, 2009–2018 - Dudognon, Danaé; Levy, Corinne; Chalumeau, Martin; Biscardi, Sandra; Dommergues, Marie-Aliette; Dubos, François; Levieux, Karine; Aurel, Marie; Minodier, Philippe; Zenkhri, Ferielle; Mezgueldi, Ellia; Craiu, Irina; et al. (Frontiers in Pediatrics, 2021)
Objective(s): Blood cultures (BC), when performed in children seen in the emergency department with community-acquired pneumonia (CAP), are most of the time sterile. We described the diagnostic accuracy of white blood cells (WBC), absolute neutrophils count (ANC), C-reactive protein (CRP) and procalcitonin (PCT) to predict blood culture (BC) result in childhood CAP. Study design: Secondary analysis of a prospective study carried out in eight pediatric emergency departments (France, 2009-2018), including children (≤ 15 years) with CAP. Analyses involved univariate comparisons and ROC curves. Results: We included 13,752 children with CAP. BC was positive in 137 (3.6%) of the 3,829 children (mean age 3.7 years) in whom it was performed, mostly with Streptococcus pneumoniae (n=107). In children with bacteremia, ANC, CRP and PCT levels were higher (median 12,256/mm3 vs. 9,251/mm3, 223 mg/L vs. 72 mg/L and 8.6 ng/mL vs. 1.0 ng/mL, respectively; p ≤0.002), but WBC levels were not. The area under the ROC curve of PCT (0.73 [95%CI 0.64-0.82]) was significantly higher (p ≤0.01) than that of WBC (0.51 [0.43-0.60]) and of ANC (0.55 [0.46-0.64]), but not than that of CRP (0.66 [0.56-0.76]; p =0.21). CRP and PCT thresholds that provided a sensitivity of at least 90% were 30 mg/L and 0.25 ng/mL, respectively, for a specificity of 25.4% and 23.4%, respectively. CRP and PCT thresholds that provided a specificity of at least 90% were 300 mg/L and 20 ng/mL, respectively, for a sensitivity of 31.3% and 28.9%, respectively. Conclusions: PCT and CRP are the best routinely available predictive biomarkers of bacteremia in childhood CAP.